PENGARUH WORKING CAPITAL TURNOVER DAN QUICK RATIO TERHADAP RETURN ON ASSETS PADA PT GAJAH TUNGGAL Tbk PERIODE 2012-2023 - Meisya Sofianti, Sastia; Nur’aidawati, Siti (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Working Capital Turnover and Quick Ratio on Return on Assets at PT Gajah Tunggal Tbk for the period 2012-2023. The type of research used is quantitative research using descriptive methods. The population in this study were all financial statements of PT Gajah Tunggal Tbk listed on the IDX. While the sample used is the Balance Sheet and Income Statement at PT Gajah Tunggal Tbk from 2012 - 2023. The data analysis method uses multiple linear regression tests, the coefficient of determination, partial t tests and simultaneous F tests. The results showed no partial positive effect of Working Capital Turnover on Return on Assets where the t-count value of 2.075470 < t-table 2.262 with a Prob. value of 0.0678> 0.05. Quick Ratio has no partial positive effect on Return on Assets where the t-count value is 2.048754 < t-table 2.262 with a Prob. value of 0.0708 > 0.05. Simultaneously Working Capital Turnover and Quick Ratio do not have a positive effect on Return on Assets where the F-count value is 2,408669 < F-table 4,256 with a Prob. (F-statistic) value of 0.145272 > 0.05. while the coefficient of determination (R²) value is 21.97%, the remaining 78.03% is influenced by other variables not examined.